Polymer Template Synthesis of Flexible BaTiO3 Crystal Nanofibers. (9th October 2019) - Yan, Jianhua; Han, Yuhui; Xia, Shuhui; Wang, Xiao; Zhang, Yuanyuan; Yu, Jianyong; Ding, Bin
Abstract: BaTiO3 crystals are attractive materials due to their high dielectric properties, but they are brittle and inelastic ceramics, which limits their broader applications in emerging fields, such as flexible electronics. A scalable strategy for the fabrication of ultra‐flexible crystalline BaTiO3 nanofiber (NF) films by a sol–gel electrospinning method, followed by a brief calcination, is reported. It facilitates the formation of perovskite BaTiO3 crystals with intricate grain boundaries at a low temperatures by growing them within polymer NF templates. The ceramic films have a polymer‐like softness of 50 mN, a large Young's modulus of 61 MPa, and an elastic strain of 0.9%. Moreover, they have a low density of 28 mg cm −3 and demonstrate superior softness without fracture after deformation. Piezoelectric sensors fabricated based on these films exhibit a high sensitivity of 80 ms with an output voltage of 1.05 V at a pressure of 100 kPa. This approach allows for the large‐scale fabrication of flexible BaTiO3 crystal NF films. Abstract : Large‐scale BaTiO3 crystal nanofiber films with superior flexibility are fabricated using a sol–gel electrospinning technique followed by calcination. These flexible films with piezoelectric properties and excellent mechanical integrity are good candidate materials for designing highly sensitive piezoelectric sensors to transform small mechanical pressure into electronic signals, expanding the application prospect of BaTiO3 crystals in flexible electronics.